Estimating Students' Satisfaction with Web Based Learning System in Blended Learning Environment. (22nd April 2014) - Bauk, Sanja; Šćepanović, Snežana; Kopp, Michael
Abstract : Blended learning became the most popular educational model that universities apply for teaching and learning. This model combines online and face-to-face learning environments, in order to enhance learning with implementation of new web technologies and tools in learning process. In this paper principles of DeLone and Mclean success model for information system are applied to Kano two-dimensional model, for categorizing quality attributes related to satisfaction of students with web based learning system used in blended learning model. Survey results are obtained among the students at "Mediterranean" University in Montenegro. The (dys)functional dimensions of Kano model, including Kano basic matrix for assessment of the degree of students' satisfaction level, have been considered in some more detail through corresponding numerical, graphical, and statistical analysis.